Предмет: Алгебра, автор: vladr6007

Помогите дам 60б..... ​

Приложения:

Ответы

Автор ответа: homasphoenix
2

Объяснение:

(1) 3/(x^2-2x+1) + 2/(1-x^2) = 1/(x+1)

3/(x-1)^2 + 2/(x-1)(x+1) - 1/(x+1) = 0

(3x+3)/(x-1)(x-1)(x+1) + (2x-2)/(x-1)(x-1)(x+1) - (x-1)(x-1)/(x-1)(x-1)(x+1) = 0

3x + 3 + 2x - 2 - (x-1)^2 = 0

5x + 1 - x^2 + 2x - 1 = 0

x^2 - 7x = 0

x(x-7) = 0

x1 = 0, x2 = 7
(2) 4/(x^2+6x+9) - 6/(9-x^2) = 1/(x-3)

4/(x+3)^2 - 6(x-3)(x+3) - 1/(x-3) = 0

(4x-12)/(x-3)(x+3)^2 - (6x + 18)/(x-3)(x+3)^2 - (x+3)^2/(x-3)(x+3)^2 = 0

4x - 12 - 6x - 18 - (x+3)^2 = 0 (x не равно 3,-3)

-2x - 30 - x^2 - 6x - 9 = 0

x^2 + 8x + 39 = 0

Немає коренів

Похожие вопросы